Creative bureaucracy: Balancing power in irrigation administration in northern Ghana - Wolfram Laube (University of Bonn, Center for Development Research (ZEF), 2009)
Since irrigation development in northern Ghana has started, the natural resources water and land within irrigation schemes have officially become the property of the government. The management of these resources has been put in the hands of an irrigation bureaucracy that is supposed to ensure a sustainable and efficient use of these resources. However, the irrigation bureaucracy does not operate in a vacuum. The irrigation bureaucracy's control over land is contested and land use decisions are influenced by various actors, such as farmers, village committees, chiefs, earth priests and local politicians, which pursue their own political interests and refer to local institutional frameworks that collide with official legislation. To maintain their control of resources, irrigation bureaucrats need to carefully balance power and interests. State bureaucrats rather than taking hegemonic decisions - try to negotiate resources and outwit other actors in order to maintain authority and obtain legitimacy, even if they are not always able to determine actual decision making. In order to live up to their responsibility, and to defend their authority, they not only refer to power and legislation emanating from the state, but take a pragmatic/opportunistic approach in which short-term alliances with local 'big men' as well as references to 'traditional' and 'neo-traditional' norms are of importance. This typical for the performance of African bureaucracies in (rural) areas where state hegemony has been partially established, but where the control of resources continues to be negotiated between different powerful actors, with reference to competing institutional regimes. Here, administration is less bureaucratic control via a fixed set of official regulations, but the creative working of political arenas that are earmarked by competing sources of power and normative frameworks.
Keywords: 330